Integration of Soft Skills and Total Quality Management as a Strategy for Vocational Education Quality Management - Putri, Ratih Erissa; Damnur, Juliani; Supianto; Hasri, Salfen; Sohiron (JIE (Journal of Islamic Education), 2025)
This study aims to analyze the integration patterns of soft skills within the principles of Total Quality Management (TQM) and examine their managerial implications for improving educational quality at SMK Muhammadiyah Pekanbaru. A qualitative case study approach was employed, conducted simultaneously across three institutions: SMK Muhammadiyah 1, 2, and 3 Terpadu Pekanbaru. Data were collected through in-depth interviews, participatory observation, and documentation studies, subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, and validated through source triangulation, technique triangulation, member checking, and thick description. The findings reveal that the integration of soft skills within TQM principles across the three schools is systematically embedded throughout all dimensions of school management, encompassing customer focus, quality-oriented leadership, human resource involvement, the PDCA cycle, and continuous improvement. Soft skills do not serve as supplementary elements; rather, they are substantial components that organically drive a quality culture, further reinforced by Islamic institutional identity as an accelerator of organizational transformation. The managerial implications produced are multilayered and transformative, covering organizational culture strengthening, human resource capacity development, character-based curriculum restructuring, industrial partnership expansion, and the establishment of an autonomous and adaptive internal quality assurance system. This study proposes that the sustainability of vocational education quality is achievable only when soft skills become an integral part of the school's organizational DNA. These findings contribute to achieving SDG Goals 4 and 8 by preparing technically excellent graduates who are characterologically mature and globally competitive.